Hepatitis C vaccine clinical trials among people who use drugs: potential for participation and involvement in recruitment - Young, April M. (Contemp Clin Trials, 2014)
Candidate prophylactic HCV vaccines are approaching phase III clinical trial readiness, yet little is known about the potential for participation among target groups or innovative ways to promote enrollment within ‘hard-to-reach’ populations. This study describes HCV vaccine trial participation willingness among a high-risk sample of people who use drugs and their willingness to assist researchers by promoting the trial among peers. Willingness to participate in and encourage peers’ participation in an HCV vaccine trial was assessed among injection and non-injection drug users enrolled in a cohort study in Kentucky using interviewer-administered questionnaires (n=165 and 415, respectively, with willingness to participate assessed among HCV-seronegative participants only). Generalized linear mixed models were used to determine correlates to being "very likely" to participate or encourage participation in a trial. Most reported being likely to participate or encourage participation in a vaccine trial (63% and 87%, respectively). Men were significantly less likely to report willingness to encourage others’ participation, while willingness to encourage was higher among HCV-seropositive participants. Unemployment, lesser education, receipt of financial support from more peers, and nonmedical prescription drug use were positively associated with willingness to participate, as were heroin and methamphetamine use. Differential enrollment in HCV vaccine clinical trials by socioeconomic status may occur, underscoring ethical considerations and need for avoiding coercion. Notably, the data suggest that a peer-driven approach to promoting trial participation among people who use drugs could be feasible in this population and that HCV-seropositive individuals and women could be especially instrumental in these efforts.